2020
DOI: 10.1002/jbt.22440
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 and calcium cosupplementation alleviates cadmium hepatotoxicity in the rat: Enhanced antioxidative and anti‐inflammatory actions by remodeling cellular calcium pathways

Abstract: Although vitamin D (VD) and calcium (Ca) attenuate cadmium (Cd) metabolism, their combined antioxidant and anti‐inflammatory actions against Cd toxicity have not been previously explored. Hence, this study measured the protective effects of VD ± Ca supplements against Cd hepatotoxicity. Forty adult male rats were distributed to: negative controls (NCs), positive controls (PCs), VD, Ca, and VD3 and Ca (VDC) groups. All groups, except NC, received CdCl2 in drinking water (44 mg/L) for 4 weeks individually or con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Euthanasia was then performed on day-15 by cervical dislocation under anesthesia as previously reported. 18 Blood samples were obtained, and serum was kept at −20°C following centrifugation. Both kidneys were removed from each rat, and a specimen was used for histopathological experiments.…”
Section: Types Of Samplesmentioning
confidence: 99%
“…Euthanasia was then performed on day-15 by cervical dislocation under anesthesia as previously reported. 18 Blood samples were obtained, and serum was kept at −20°C following centrifugation. Both kidneys were removed from each rat, and a specimen was used for histopathological experiments.…”
Section: Types Of Samplesmentioning
confidence: 99%
“…It has been reported that the content of Ca in body can significantly influence Cd absorption in the gastrointestinal tract, for Cd use the same intestinal transporters as Ca in both animals and humans [ 17 , 21 ]. With a high chemical similarity to Cd, Ca can regulate physiological or metabolic changes in organisms induced by Cd [ 33 ]. In our study, all indicators in Ca-group were not significantly different from those in control-group, which excluded the threat of Ca supplementation on the health of mice, whereas there was significant toxicity of liver and kidneys in mice exposed to Cd as compared with the mice in control-group.…”
Section: Discussionmentioning
confidence: 99%
“…Cd is an indirect genotoxic carcinogen, and it has been shown that chronic Cd exposure strongly correlates with an increased risk of several cancers including prostate, genitourinary, breast, lung, pancreas, and hepatocellular carcinoma (HCC) [25][26][27][28][29][30] mechanism of Cd carcinogenesis has shown that chronic Cd exposure can induce oxidative stress [31][32][33], inhibit DNA repair [34,35], promote abnormal methylation of DNA [36][37][38], interfere with gene expression [29,38], affect cell cycle regulation [39,40], inhibit cell apoptosis [41], induce inflammatory signaling [42], and promote genomic instability and mutation in key genes to promote tumorigenesis [43]. Indeed, high concentrations of Cd from acute exposure or low concentrations of chronic exposure are both linked to severe hepatotoxicity/liver injury that promotes liver diseases and HCC development (Figure 2).…”
Section: Acute and Chronic CD Exposure Andmentioning
confidence: 99%